Documentary biography films violin luthiers A media education on the nivel of art work - Trilaksono, Yunanto (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2024)
The study aims to analyze the use of signs or symbols in the film to convey deeper messages or meanings as educational media about the value of artwork in the creation of violin instruments in Sidoarjo. The film can be considered as an educational medium because it provides information about the process of making violin instruments in detail. The film can provide knowledge of the materials used, manufacturing techniques, and crafts required in making violin instruments. In addition, the film can also provide an understanding of the value of art in the manufacture of violin instruments. In the film, it may be shown that the creation of violin instruments requires high precision, expertise and dedication. This shows that artwork in the manufacture of violin instruments is not only a technical process, but also involves aspects of art and beauty. This documentary can also provide an understanding of the cultural value and local heritage. In the film, it may be shown that the creation of violin instruments in Sidoarjo has a high cultural value. This enriches our understanding of the diversity of Indonesian culture and increases our appreciation of local crafts. In addition, this documentary can also provide inspiration for audiences interested in art and music. The film can motivate them to develop their interest in the art of making violin instruments or even in the art of the whole. By conducting an in-depth analysis of this documentary, we can understand the art and cultural values of the creation of violin instruments at Sidoarjo and appreciate local crafts. The film can also be an effective educational medium for those interested in art and music.